폴리락타이드 스테레오 콤플렉스 형성을 이용한 주입형 하이드로젤의 합성 및 특성평가 - 전여진 (The Graduate School, Ajou University, 2009)
Injectable hydrogels are quite promising materials because they have the potential to minimize invasive implantation, which provide versatile fitness irrelevant to the damaged regions and facilitate the incorporation of bioactive agents or cells. In situ gel formation through stereocomplex formation is a promising candidate for injectable hydrogels. In this paper, a new series of enantiomeric 4-arm PEG-PLA block copolymers and their stereocomplexed hydrogels were prepared by bulk ring-opening polymerization of D-lactide and L-lactide, respectively, with stannous octoate as a catalyst. The prepared polymers were characterized by 1H NMR, FT IR, GPC and TGA, confirming the tailored structure and chain lengths. The swelling and degradation behavior of the hydrogels formed from a selected copolymer series are observed in different concentrations. The results showed that a larger portion of the polymers in a solution induced a slower degradation rate. The rheological behavior indicated that the prepared hydrogel underwent in situ gelation and had favorable mechanical strength. In addition, its feasibility as an injectable scaffold was evaluated using a media dependence test for cell culture. It was found that a Tris solution was more favorable for in situ gel formation than PBS and DMEM solutions. These results suggest that in situ forming hydrogel through the construction of a stereocomplex with enantiomeric 4-arm PEG-PLA copolymers was accomplished. Overall, enantiomeric 4-arm PEG-PLA copolymers are new species of stereocomplexed hydrogels that are suitable for further research into injectable hydrogels.
학위논문(석사)--아주대학교 일반대학원 :분자과학기술학과,2009. 2
Keywords: stereocomplexed hydrogel